MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
Menu
anirudh alameluvari Grade: Upto college level
        

          x3/ x3+27+9x(x+3)    =    x-3 / x+6

8 years ago

Answers : (1)

mycroft holmes
266 Points
										

We are given that x3/(x+3)3 = x-3/(x+6). From componendo-dividendo, we get


 


(x+3)3-x3/(x+3)3+x3 = (x+6) - (x-3)/(x+6) + (x-3)


 


or 3 [x2+(x+3)2 + x(x+3)]/(2x+3)(x2+(x+3)2-x(x+3)] = 9/(2x+3)


 


So, either x = -3/2 or 3[x2+(x+3)2-x(x+3)] = x2+(x+3)2 + x(x+3)


 


The second equation would imply 9 = 0 and hence x = -3/2 is the only possibility


 

8 years ago
Think You Can Provide A Better Answer ?
Answer & Earn Cool Goodies
  • Complete JEE Main/Advanced Course and Test Series
  • OFFERED PRICE: Rs. 15,900
  • View Details

Ask Experts

Have any Question? Ask Experts

Post Question

 
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!! Click Here for details